Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1177/154596830201600307
|View full text |Cite
|
Sign up to set email alerts
|

Modified Constraint-Induced Therapy after Subacute Stroke: A Preliminary Study

Abstract: mCIT may be an efficacious method of improving affected arm function and use in stroke patients exhibiting learned nonuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Derived from basic studies in animals, CIMT combines repetitive task practice (RTP) with shaping, 4 during which participants engage in meaningful functional activities with measurable progressions for which they receive positive feedback as the activities become increasingly more difficult; behavioural re-training (e.g., behavioural contract, problem solving to address barriers to affected limb use); and restraint of the unaffected UE. 4,5 Several CIMT protocols have been developed, including a ''traditional'' or massed practice approach, a ''non-traditional'' or distributed practice approach, 4,[6][7][8][9] and variations on these two approaches. 10,11 Traditional CIMT involves six hours a day of RTP combined with restraint of the unaffected UE for 90% of waking hours over 10 consecutive weekdays (therapy sessions do not occur on weekends).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Derived from basic studies in animals, CIMT combines repetitive task practice (RTP) with shaping, 4 during which participants engage in meaningful functional activities with measurable progressions for which they receive positive feedback as the activities become increasingly more difficult; behavioural re-training (e.g., behavioural contract, problem solving to address barriers to affected limb use); and restraint of the unaffected UE. 4,5 Several CIMT protocols have been developed, including a ''traditional'' or massed practice approach, a ''non-traditional'' or distributed practice approach, 4,[6][7][8][9] and variations on these two approaches. 10,11 Traditional CIMT involves six hours a day of RTP combined with restraint of the unaffected UE for 90% of waking hours over 10 consecutive weekdays (therapy sessions do not occur on weekends).…”
mentioning
confidence: 99%
“…4,6 Conversely, modified CIMT, a nontraditional protocol, takes place over a 10-week period, involving RTP for 30 minutes/day, 3Â/week, combined with 5 hours/day of unaffected UE restraint. 7,8 Regardless of the specific protocol used, the client is generally required to have a degree of movement in the affected UE that, at a minimum, includes 10 of active wrist extension with a 10 extension of the thumb and at least two fingers. 6,7 The need for this level of function and the corresponding capacity for active engagement with the treatment limits the number of people for whom CIMT is an appropriate intervention.…”
mentioning
confidence: 99%
“…According to Langhorne's report, mental practice (motor imagery training) seems most effective for upper extremity function when conducting meta-analysis. Therefore, this report has shown that motor imagery training had a greater effect than other interventions in established clinical evidence, such as constraint-induced movement therapy [18][19][20][21] (where patients are asked to use an affected limb (execute a task) for a long time and for a large number of repetitions under the condition that the intact limb is constrained), robot-assisted therapy [22,23] (where robotic devices can assist patients' affected limb use in high-intensity, repetitive, specific task by digital control), and electrical interface [24] (where electrostimulation can deliver electric impulses to the muscle through the skin surface and elicit muscle contraction by simulating the neuromuscular system; the intensity, frequency, and patterns of impulse delivery can be selected depending on the patient's condition). The reports investigating the effects of motor imagery training are increasing; however, it must be considered that there are still a very few number of reports verifying the beneficial effects of motor imagery training.…”
Section: Motor Imagery Trainingmentioning
confidence: 75%
“…Based on this information, several authors modified the applicability of the technique in order to facilitate its use for both the therapist and the patient [10,13,18,53,54].…”
Section: Several Investigations Have Been Conducted In Order Tomentioning
confidence: 99%
“…At home, the patient uses the immobilizer on the affected limb 5 hours a day, 5 days a week for 10 weeks [17,18,54]. In another protocol the patient trains 5 hours per day (2 morning hours and 3 afternoon hours) for two consecutive weeks.…”
Section: Several Investigations Have Been Conducted In Order Tomentioning
confidence: 99%